INTERNALIZATION OF INCLUSIVE EDUCATION THROUGH CHILDREN'S LITERATURE WITH DISABILITY THEME - Zahro, Diyan Fatimatuz; Haryati, Isti; Setiawan, Akbar Kuntardi (Universitas Negeri Makassar, 2024)
The aim of this study is to describe the internalization of inclusive education through children's literature with the theme of disability. The research data are words, phrases and sentences in the children's book Meine Füße sind der Rollstuhl, which shows the internalization of inclusive education values, shown by the character Margit, and other characters. The research data source is the children's story Meine Füße sind der Rollstuhl, written by Franz-Joseph Huainigg, published in 2003. Data collection involved utilizing note-taking techniques to capture key aspects of the narrative. Subsequently, all gathered data underwent analysis using both a referential identity approach and reflective, introspective methods. The results of this study show that literary works, especially children's literature, can be a beneficial media for internalizing inclusive education. The introduction and internalization of inclusion education values through children's literature with disability themes is relevant to develop children’s positive character. It is in consonance with what Horace stated about the function of literature that not only entertains but also educates. The internalization of inclusive education values through disability-themed children's literature, both receptively and productively, is expected to help overcome the problems of implementing inclusive education in Indonesia so that equality in education, as all people aspire to, can be realized.